2006
DOI: 10.1039/b601669c
|View full text |Cite
|
Sign up to set email alerts
|

Extremely strong solvent dependence of the S1→ S0internal conversion lifetime of 12′-apo-β-caroten-12′-al

Abstract: The ultrafast internal conversion (IC) dynamics of the carbonyl carotenoid 12'-apo-beta-caroten-12'-al has been investigated in solvents of varying polarity using time-resolved femtosecond transient absorption spectroscopy. The molecules were excited to the S(2) state by a pump beam of either 390 or 470 nm. The subsequent intramolecular dynamics were detected at several probe wavelengths covering the S(0)--> S(2) and S(1)--> S(n) bands. For the S(1)--> S(0) internal conversion process, a remarkably strong acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
103
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(126 citation statements)
references
References 27 publications
16
103
1
4
Order By: Relevance
“…To account for this observation, an intramolecular charge transfer (ICT) state has been postulated to exist in the excited singlet state manifold (Bautista et al 1999a;Frank et al 2000). This idea has been supported by theoretical computations (Vaswani et al 2003) and experiments on numerous carbonyl-containing carotenoids and polyenals Kopczynski et al 2007;Kusumoto et al 2010;Papagiannakis 2004;Premvardhan et al 2005;Stalke et al 2008;Van Tassle et al 2007;Wild et al 2006;Zigmantas et al 2001Zigmantas et al , 2002Zigmantas et al , 2003Zigmantas et al , 2004. The studies suggest that alterations in the polarity of amino acids in the vicinity of peridinin bound in its natural protein environment may provide a mechanism by which light-harvesting may be regulated in the PCP complex (Polívka et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…To account for this observation, an intramolecular charge transfer (ICT) state has been postulated to exist in the excited singlet state manifold (Bautista et al 1999a;Frank et al 2000). This idea has been supported by theoretical computations (Vaswani et al 2003) and experiments on numerous carbonyl-containing carotenoids and polyenals Kopczynski et al 2007;Kusumoto et al 2010;Papagiannakis 2004;Premvardhan et al 2005;Stalke et al 2008;Van Tassle et al 2007;Wild et al 2006;Zigmantas et al 2001Zigmantas et al , 2002Zigmantas et al , 2003Zigmantas et al , 2004. The studies suggest that alterations in the polarity of amino acids in the vicinity of peridinin bound in its natural protein environment may provide a mechanism by which light-harvesting may be regulated in the PCP complex (Polívka et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…[15][16][17][18][19] Interestingly, this correlation was not followed by a large range of ILs. 20 The lifetime of the S 1 /ICT state in these ILs was comparable to that in solvents such as ethanol or methanol, and thus the probe's local environment appears to be considerably more polar than the dielectric constants from DRS suggest.…”
Section: Introductionmentioning
confidence: 98%
“…3 We recently demonstrated that the lifetime t 1 of the S 1 /ICT state of 12 0 CA and related apocarotenoids with terminal carbonyl-substitution strongly depends on the dipolarity of the solvent. [15][16][17]19,21 Specifically for 12 0 CA in organic solvents, we established a smooth correlation between t 1 and the polarity parameter Df. This is shown in Fig.…”
mentioning
confidence: 99%
“…[17][18][19] The chemical structures of both apocarotenals are shown in Figure 1. The 12′C species is of particular interest, because we previously found a pronounced polarity dependence of the lifetime τ 1 of its first electronically excited state ("S 1 /ICT"), varying between 220 ps in n-hexane and 8 ps in methanol, which correlated well with the polarity parameter ∆f.…”
Section: Introductionmentioning
confidence: 99%